Anti-Angiogenic Screening of Moringa Oleifera Leaves Extract Using Chorioallantonic Membrane Assay - Nisha Shri Chengama Raju; Wong Wing Kei (College of Pharmacy University of Baghdad, 2022)
Background: Angiogenesis is defined as the formation of new blood vessels. However, angiogenesis in cancer will lead to tumour growth and metastasis. Therefore, anti-angiogenesis is one of the ways to slow down growth and spreading of tumour. Moringa oleifera is also known as a "Miracle tree" which has high nutritive value and various therapeutics effect in different parts of the plant. This study aims to determine the anti-angiogenic property of Moringa oleifera leaves extract by using chick chorioallantoic membrane (CAM) assay. Materials and Methods: The extracts were prepared by decoction method using methanol and water. The qualitative phytochemical screening was carried out for both methanol and aqueous extracts. The fertilised chicken eggs were divided into six groups which include negative control group (phosphate-buffer saline with pH 7.4), positive control group (sunitinib), 50% and 100% methanol extract, 50% and 100% aqueous extract. The anti-angiogenic effect of Moringa oleifera leaves extract was determined by calculating the number and percentage decrease in blood vessels in post-24 and post-48 hours of treatment. Results: Statistical analysis by one-way ANOVA has shown significant (p<0.05) percentage reduction in the blood vessels between each treatment group after 48 hours of treatment. Among all the extracts, 100% aqueous extract of Moringa oleifera was found to have highest anti-angiogenic effect with the greater percentage decrease in blood vessels (81.33%) in post-48 hours of treatment. Furthermore, the anti-angiogenic effect of Moringa oleifera leaves was found to increased when the concentration of the Moringa oleifera extract was increased. Conclusion: Moringa oleifera leaves with various phytochemicals was found to possess anti-angiogenic potential.